Beberapa Aspek Epistemologi: Konsep, Tabiat dan Sumber-Sumber Ilmu dalam Tradisi Islam - Husin, Basri (Jurnal Usuluddin, 2009)
This article focuses on some aspects of Islamic epistemology which includes the concepts, natures and sources of knowledge in Islam. In general epistemology is a discipline to discuss and investigate the origins, sources, methods, processes and limits of knowledge or the knowledge to bring to an understanding of the intrinsic truth. In Islamic tradition, a knowledge obtained should achieve the level of confidence for the final goal of a thing is to have elements of truth in absolute terms. In terms of the truth of knowledge, the rules of Islamic epistemology considers knowledge as something possible and rejects the opinion of the skeptic who considers knowledge as an impossibility. While in terms of knowledge, the concept of Islamic epistemology based on faith worldview is not only limited to the acquisition of resources to al-khabar al-sadiq and intuition only, but also give space to the mind and senses to gain knowledge on the scope of which could achieved by the faculty of mind and senses.